Детективные романы и повести: [Перевод] / Агата Кристи - Кристи Агата (Книжное издательство, 1990)
Экземпляры: ф. 19 (20220722) / Инвентарный номер: 27530 / Цена: 5000.00 / Авт.знак: К82 / ГРНТИ: 17.82 / ББК: 84(Вел)